Estrogenic Effects of Several BPA Analogs in the Developing Zebrafish Brain - Cano-Nicolau, Joel; Vaillant, Colette; Pellegrini, Elisabeth; Charlier, Thierry D.; Kah, Olivier; Coumailleau, Pascal (Frontiers in Neuroscience, 2016)
Important set of studies have demonstrated the endocrine disrupting activity of Bisphenol A (BPA). The present work aimed at defining estrogenic-like activity of several BPA structural analogs, including BPS, BPF, BPAF, and BPAP, on 4-day or 7-day post-fertilization (dpf) zebrafish larva as an in vivo model. We measured the induction level of the estrogen-sensitive marker cyp19a1b gene (Aromatase B), expressed in the brain, using three different in situ/in vivo strategies: 1) Quantification of cyp19a1b transcripts using RT-qPCR in wild type 7-dpf larva brains exposed to bisphenols ; 2) Detection and distribution of cyp19a1b transcripts using in situ hybridization on 7-dpf brain sections (hypothalamus); and 3) Quantification of the cyp19a1b promoter activity in live cyp19a1b-GFP transgenic zebrafish (EASZY assay) at 4-dpf larval stage. These three different experimental approaches demonstrated that BPS, BPF or BPAF exposure, similarly to BPA, significantly activates the expression of the estrogenic marker in the brain of developing zebrafish. In vitro experiments using both reporter gene assay in a glial cell context and competitive ligand binding assays strongly suggested that up-regulation of cyp19a1b is largely mediated by the zebrafish estrogen nuclear receptor alpha (zfERα). Importantly, and in contrast to other tested bisphenol A analogs, the bisphenol AP (BPAP) did not show estrogenic activity in our model.